Endoscope-Assisted Pedicled Maxillary Artery to Middle Cerebral Artery Bypass: An Anatomic Feasibility Study. Issue 2 (18th February 2023) - Samarage, Hasitha Milan; Kim, Wi Jin; Zarrin, David A.; Goel, Keshav; Kim, Won; Bergsneider, Marvin; Wang, Marilene B.; Suh, Jeffrey D.; Lee, Jivianne T.; Colby, Geoffrey P.; Johnson, Jeremiah N.; Peacock, Warwick J.; et al.
Abstract : BACKGROUND: Extracranial to intracranial bypass is used to augment and/or replace the intracranial circulation for various pathologies. The superficial temporal artery is the mainstay donor for pedicled bypasses to the anterior circulation but can be limited by its variable size, low native flow rates, and potential scalp complications. Interposition grafts such as the radial artery or greater saphenous vein are alternatives but are sometimes limited by size mismatch, length needed to reach the extracranial circulation, and loss of inherent vascular elasticity. Interposition grafts between the maxillary artery (IMA) and middle cerebral artery (MCA) address these limitations. OBJECTIVE: To explore the feasibility of harvesting the IMA through an endoscopic transnasal, transmaxillary approach to perform a direct IMA to MCA bypass. METHODS: Combined transcranial and endoscopic endonasal dissections were performed in embalmed human cadavers to harvest the IMAs for intracranial transposition and direct anastomosis to the MCA. Donor and recipient vessel calibers were measured and recorded. RESULTS: A total of 8 procedures were performed using the largest and distal-most branches of the IMA (the sphenopalatine branch and the descending palatine branch) as pedicled conduits to second division of middle cerebral artery (M2) recipients. The mean diameter of the IMA donors was 1.89 mm (SD ± 0.42 mm), and the mean diameter of the recipient M2 vessels was 1.90 mm (SD ± 0.46 mm). CONCLUSION: Endoscopic harvest of the IMA using a transnasal, transmaxillary approach is a technically feasible option offering an excellent size match to the M2 divisions of the MCA and the advantages of a relatively short, pedicled donor vessel.